A fuzzy data-driven reliability analysis for risk assessment and decision making using Temporal Fault Trees - Kabir, Sohag (Decision analytics journal, 2023)
Fuzzy data-driven reliability analysis has been used in different safety-critical domains for risk assessment and decision-making where precise failure data is non-existent. Expert judgements and fuzzy set theory have been combined with different variants of fault trees as part of fuzzy data-driven reliability analysis studies. In such fuzzy fault tree analyses, different people represented failure data using different membership functions for the fuzzy set, and different parameters were set differently in the expert opinion elicitation process. Due to the availability of a wide variety of options, it is possible to obtain different outcomes when choosing one option over another. This article performed an analysis in the context of fuzzy data-based temporal fault tree analysis to investigate the effect of choosing different membership functions on the estimated system reliability and criticality ranking of different failure events. Moreover, the effect of using different values for the relaxation factor, a parameter set during the expert elicitation process, was studied on the system reliability and criticality evaluation. The experiments on the fuel distribution system case study show system reliability did not vary when triangular and trapezoidal fuzzy numbers were used with the same upper and lower bounds. However, it was seen that the criticality rankings of a couple of events were changed due to choosing different membership functions and different values of relaxation factor •Study uncertainty sensitivity analysis in fuzzy temporal fault tree analysis.•Combine expert judgements and fuzzy set theory with different variants of fault trees.•Analyse the effects of different membership functions on system reliability and components’ criticality.•Evaluate effects of choosing different relaxation factors during expert opinion elicitation.•Choosing different membership functions and different values of relaxation factor may yield different outcomes.